Digital Humanities in the India Rim (Open Book Publishers, 2024)
This varied collection delves into illuminating examples of Digital Humanities research and practice currently being undertaken by academics in India and Australia, and seeks to understand the shared challenges as well as the points of similarity and difference between them. From the influence of Netflix on International Relations to contemporary digital adaptations of Mary Shelley’s Frankenstein, via detours into erobotics (empathic robots) and the cultural specificity of online dating, these essays convey the distinctive breadth and imagination of research in this field. Digital Humanities is a relatively new discipline in the India Rim, and this novelty has created space for innovative research ideas, as well as the use of traditional methodologies and software in different ways within these unique cultural spaces that could potentially influence how Digital Humanities is conceptualised internationally. For example, drawing on Indian classical logic leads to novel designs and applications of computation. This lively volume offers a fresh look at the Digital Humanities and an important overview of the work taking place in a region other than the Western countries that typically dominate the field. It has much to offer both experienced researchers and those new to the Digital Humanities.